2018
DOI: 10.1093/infdis/jiy375
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Toxoplasma gondii DNA Samples Isolated From Humans Living in North America: An Unexpected High Prevalence of Atypical Genotypes

Abstract: Clinicians should be aware that atypical genotypes are common in North America and have been associated with severe ocular and systemic disease and unusual presentations of toxoplasmosis in immunocompetent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…In a recent retrospective study on 76 clinical samples, the relative sensitivity of B1 qPCR was shown to be only 54% of that of Rep 529 qPCR (4). However, whereas there is high genetic homogeneity of strains circulating in Europe, particularly in France, much greater heterogeneity has been recently highlighted in the United States, but less than in South America (26). The sensitivity of the Rep 529 target was questioned for non-type II T. gondii isolates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent retrospective study on 76 clinical samples, the relative sensitivity of B1 qPCR was shown to be only 54% of that of Rep 529 qPCR (4). However, whereas there is high genetic homogeneity of strains circulating in Europe, particularly in France, much greater heterogeneity has been recently highlighted in the United States, but less than in South America (26). The sensitivity of the Rep 529 target was questioned for non-type II T. gondii isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Selected samples were sent to laboratory 1 as part of routine diagnosis and treatment with no unnecessary invasive procedures. Genotyping data obtained by microsatellite analysis were available for 34 samples from a previous study (26). Thirteen isolates belonged to type II, 5 to type III, and 16 to atypical lineages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most infections in humans are asymptomatic. However, severe complications may occur during (i) congenital Toxoplasma infection, such as abortion, stillbirth and hydrocephalus in new-borns [1,4,5]; (ii) ocular toxoplasmosis, with retinochoroidal lesions leading to chronic ocular disease [1,2]; (iii) encephalitis in immunosuppressed patients [1,4,5]; and (iv) multivisceral toxoplasmosis due to atypical genotypes in South America [6][7][8]. A possible implication of T. gondii genetic diversity on the pathogenesis of toxoplasmosis has been postulated [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental feeding of cats may alter T. gondii transmission by changing cat distribution, demographics and exposure to infected prey (Schmidt et al, ; VanWormer et al, ). Furthermore, free‐roaming cats in central California, USA are known reservoirs of atypical T. gondii genotypes (e.g., Type X) (VanWormer et al, ), which are associated with more severe disease in people (Blaizot et al, ; Carme et al, ; Pomares et al, ). Understanding the risks of exposure to T. gondii from contaminated soil will help inform management of free‐roaming cat colonies and assess the risk of human exposure to this zoonotic pathogen.…”
Section: Introductionmentioning
confidence: 99%